Radotinib inhibits mitosis entry in acute myeloid leukemia cells via suppression of Aurora kinase A expression - Sook-Kyoung Heo; Eui-Kyu Noh; Yoo Kyung Jeong; Lan Jeong Ju; Jun Young Sung; Ho-Min Yu; Jaekyung Cheon; SuJin Koh; Young Joo Min; Yunsuk Choi; Jae-Cheol Jo (Tumor Biology)
Aurora kinases play critical roles in regulating several processes pivotal for mitosis. Radotinib, which is approved in South Korea as a second-line treatment for chronic myeloid leukemia, inhibits the tyrosine kinase BCR-ABL and platelet-derived growth factor receptor. However, the effects of radotinib on Aurora kinase expression in acute myeloid leukemia are not well studied. Interestingly, the cytotoxicity of acute myeloid leukemia cells was increased by radotinib treatment. Radotinib significantly decreased the expression of cyclin-dependent kinase 1 and cyclin B1, the key regulators of G2/M phase, and inhibited the expression of Aurora kinase A and Aurora kinase B in acute myeloid leukemia cells. In addition, radotinib decreased the expression and binding between p-Aurora kinase A and TPX2, which are required for spindle assembly. Furthermore, it reduced Aurora kinase A and polo-like kinase 1 phosphorylation and suppressed the expression of α-, β-, and γ-tubulin in acute myeloid leukemia cells. Furthermore, radotinib significantly suppressed the key regulators of G2/M phase including cyclin B1 and Aurora kinase A in a xenograft animal model. Therefore, our results suggest that radotinib can abrogate acute myeloid leukemia cell growth both in vitro and in vivo and may serve as a candidate agent or a chemosensitizer for treating acute myeloid leukemia.